Inner Speech on the Album Untuk Dunia, Cinta, dan Kotornya by Nadin Amizah - Alyani, Sita; Mukhlis, Mukhlis; Kurniawan, Latif Anshori (Journal of English Language and Education, 2025)
This study discusses inner speech in the album Untuk Dunia, Cinta, dan Kotornya by Nadin Amizah with a psycholinguistic approach. This study uses a descriptive qualitative method with reading and recording techniques for eleven songs in the album. Content analysis was used to find the types of inner speech contained in song lyrics, such as egocentric speech, rhetorical inner question, and negative self-dialogue. The album has three phases: (1) self-hatred, (2) acceptance of love from others, and (3) self-love. These three phases describe the psychological dynamics that develop from rejection to self-acceptance, in line with the concept of inner speech according to Vygotsky which serves as an introduction to self-reflection, a regulator of human emotions and behavior. These findings also reinforce the views of Alderson-Day Fernyhough (2015) and Oleś et al. (2020) on inner speech. Theoretically, this study emphasizes the relevance of the concept of inner speech in shaping the meaning of linguistic expression in popular music works. Practically, this study extends the study of psycholinguistics into the realm of Indonesian music and shows that song lyrics can serve as a medium to understand a person's cognitive and emotional dynamics.